Biodegradation of Polychlorinated Biphenyls Using Acclimadzed Biofilmina Three-Phase Fluidized Bed Aerobic Reactor - Joseph Auresenia; Donna Marie G Taleon (ASEAN Journal of Chemical Engineering, 2004)
This paper investigates the ability of microorganisms in a biofilm to degrade polychlorinated biphenyls (PCBs) using a three-phase fluidized bed aerobic biofilm reactor. Water was spiked with PCBs that contain mainly Aroclor 1260 to simulate PCB-contaminated water. The "contaminated" water was batch fed into the reactor to acclimatize the microorganisms in the biofilm. The degradation of PCBs was monitored through the decrease in concentration of Aroclor 1260. Samples were analyzed using gas chromatography equipped with an electron capture detector (ECD). Batch experimental runs with an initial concentration of around 70 ppm showed PCB degradation of up to 93% after 8 h. After the runs that usen "contaminated" water, the batch runs using feed that contain easily degradable organic chemicals were performed to determine the effect of contact with PCB on the biofilm. Their latter runs showed that the COD degradation rate had no significant difference with the COD runs before the PCB batch runs. These results showed that biofilm formed in a three-phase fluidized bed Aerobic is capable of degrading PCB in water and that the microorganisms are not significantly affected by exposure to PCB.